2010
DOI: 10.7763/ijtef.2010.v1.65
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Academic and Athletic Motivation on Academic Performance Among University Students

Abstract: Abstract-The purpose of this paper is to examine the academic and athletic motivation and identify the factors that determine the academic performance among university students in the Emirates of Dubai. The study examined motivation based on nontraditional measure adopting a scale to measure both academic as well as athletic motivation. This study involving 217 athlete and non-athlete students reveals that academic motivation, career athletic motivation and student athletic motivation are motivational factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 15 publications
8
28
1
Order By: Relevance
“…Although in the previous studies on SAMSAQ [10,11,22,23,25,26], no difference emerged in relation to gender for any factors, the findings of this study seem to confirm the above-mentioned expectations. In fact, female Italian student-athletes reported higher AM scores with respect to their males' counterparts, suggesting that the general Italian development of women's sport is not able to minimize the gender effect in sports.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Although in the previous studies on SAMSAQ [10,11,22,23,25,26], no difference emerged in relation to gender for any factors, the findings of this study seem to confirm the above-mentioned expectations. In fact, female Italian student-athletes reported higher AM scores with respect to their males' counterparts, suggesting that the general Italian development of women's sport is not able to minimize the gender effect in sports.…”
Section: Discussionsupporting
confidence: 81%
“…However, confirming the previous literature [10,20,22,23,25,26], social-cultural systems are crucial in influencing the factor structure of the instrument, determining different models suitable for different studentathletes populations. Independently of the national social and policy supports for dual career, Italian student-athletes' sport, academic, and career motivational scores resulted quite similar to those of American [11], United Arab Emirates [10], and other European [25] student-athletes. In particular, similarities emerged with the latter study, where higher, intermediate, and lower values were reported for CM, SM, and AM scores, respectively.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations